PENERAPAN MODEL CONTEXTUAL TEACHING LEARNING UNTUK MENINGKATAKAN MOTIVASI DAN HASIL BELAJAR IPA DIKELAS V/A SDN 036/VI RANTAU PANJANG III - Nurjanah; Wahyu Hidayat, Puput (Jurnal Muara Olahraga, 2024)
ABSTRACT The problem in this research is that student motivation and learning outcomes in Natural Sciences subjects for class VA SDN 36/VI Rantau Panjang III are still relatively low. The aim of this research is to describe the application of the contextual learning model in the VA class on motivation and learning outcomes. The method used in this research is classroom action research (PTK). This research consists of 2 cycles, each cycle is carried out through 4 stages, namely planning, action, observation and reflection and consists of 2 meetings. Student learning motivation can be explained as follows: (1) the application of the contextual learning model can increase student learning motivation and the results of the learning motivation questionnaire show that in cycle I there was 55.45% while in cycle II it increased very well, namely 83.50%, this indicates s=tudent learning motivation increased according to the success indicator, namely 80%. The results of this research can be explained as follows: (1) the application of the contextual learning model in learning in cycle I is still not optimal. This can be seen from the tests in cycle I. Only 60.40% of students got a score within the maximum completeness criteria and 39.60% did not reach the maximum completeness criteria. (2) Student learning outcomes improved very well in cycle II. From 45% (initial observation), to 60.40% (cycle I) and 80.00% (cycle II). Keywords: Motivation, Science Learning Outcomes, Contextual Teaching Learning Model